2020
DOI: 10.1002/jmv.25998
|View full text |Cite
|
Sign up to set email alerts
|

The impact of laryngopharyngeal reflux disease on 95 hospitalized patients with COVID‐19 in Wuhan, China: A retrospective study

Abstract: Studies have demonstrated that comorbidities, especially cardiovascular and endocrine diseases, correlated with poorer clinical outcomes. However, the impact of digestive system diseases has not been issued. The aim of this study is to determine the impact of laryngopharyngeal reflux disease (LPRD) on hospitalized patients with coronavirus disease 2019 . We extracted clinical data regarding 95 patients in Wuhan Jinyintan Hospital, Wuhan, China, between 26 January and 21 February 2020. The Reflux Symptom Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 21 publications
1
14
0
5
Order By: Relevance
“…Consistent with previous studies [ 20 ], our binary logistic regression analysis showed that age, cerebrovascular disease, and chronic renal disease were independent risk factors for death in patients with COVID-19 and diabetes. Studies have shown that hypertension was the most common comorbidity in patients with COVID-19, followed by diabetes and coronary heart disease [ 20 ], and hypertension was a risk factor for disease progression in patients with COVID-19 [ 21 ]. However, we found no association between hypertension and poor outcomes in patients with COVID-19 and diabetes, but did find an association in patients with COVID-19 without diabetes, which may demonstrate that the impact of diabetes on disease severity and mortality in patients with COVID-19 was greater than that of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies [ 20 ], our binary logistic regression analysis showed that age, cerebrovascular disease, and chronic renal disease were independent risk factors for death in patients with COVID-19 and diabetes. Studies have shown that hypertension was the most common comorbidity in patients with COVID-19, followed by diabetes and coronary heart disease [ 20 ], and hypertension was a risk factor for disease progression in patients with COVID-19 [ 21 ]. However, we found no association between hypertension and poor outcomes in patients with COVID-19 and diabetes, but did find an association in patients with COVID-19 without diabetes, which may demonstrate that the impact of diabetes on disease severity and mortality in patients with COVID-19 was greater than that of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…По результатам анализа данных 95 пациентов с COVID-19 (Ухань, Китай) у 38,9% выявили ларингофарингеальную рефлюксную болезнь (внепищеводную манифестацию ГЭРБ). Выраженность индекса симптомов рефлюкса при тяжелой и крайне тяжелой степени тяжести инфекции были достоверно выше, чем у пациентов со среднетяжелым течением заболеванием, а индекс более 13 баллов коррелировал с худшими клиническими исходами [29]. Однако, Lechien J. R. et al (2020) считают, что индекс симптомов рефлюкса не может быть достаточно специфичным для диагностики ларингофаренгиального рефлюкса у пациентов с COVID-19 вследствие того, что на наличие и выраженность его симптомов также влияет поражение СО дыхательных путей коронавирусом SARS-CoV-2 и полагают проведение дальнейших исследований [30].…”
Section: этиология и патогенезunclassified
“…We read with interest the paper entitled "The impact of laryngopharyngeal reflux disease on 95 hospitalized patients with coronavirus disease 2019 (COVID-19) in Wuhan, China: A retrospective study." 1 The authors retrospectively reported that hospitalized patients with laryngopharyngeal reflux (LPR) had poorer clinical outcomes compared with those without LPR according to reflux symptom index (RSI). The LPR diagnosis was based on RSI > 13, which is the threshold used by Belafsky et al to suspect LPR.…”
Section: The Association Between Laryngopharyngeal Reflux and Covid-1mentioning
confidence: 99%
“…Second, Jiang et al stated that the LPR prevalence was higher in their patients, suggesting a potential impact of the virus on the upper esophageal sphincter. 1 In fact, the prevalence of LPR is still unknown. 5 The studies that were cited by authors are epidemiological studies that assessed the LPR-symptoms in populations but the LPR diagnosis was not confirmed in these studies.…”
Section: The Association Between Laryngopharyngeal Reflux and Covid-1mentioning
confidence: 99%